"ANALYSIS OF ISOLATED EYE INJURIES IN LIVING INDIVIDUALS: FORENSIC MEDICAL PRACTICE IN UZBEKISTAN" - N.Kh.Ganieva; A.K.Nuridinov (Ustozlar uchun, 2025)
Isolated injuries of the visual organ are one of the complex forms of damage that require accurate forensic medical assessment. In Uzbekistan, this area is of particular importance in the context of the development of national legislation and reform of the health care system. The article examines the legal and methodological aspects of forensic medical examination of eye injuries, analyzes regional forensic medical practice, and suggests ways to improve the quality of expert opinions.